Hoop dreams [videorecording (DVD)] - James, Steve, 1955-; Agee, Arthur; Gates, William; Knight, Bobby (New Line Home Entertainment [distributor], 2005)
This documentary follows two inner-city basketball phenoms' lives through high school as they chase their dreams of playing in the NBA.